2015
DOI: 10.1016/j.rmed.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Establishing normative nasal nitric oxide values in infants

Abstract: In this study we determined a regression model that best fits normative nNO values for infants less than 1 year old. This model identified the majority of PCD infants as having abnormally low nNO. These findings suggest nNO measurement can help guide PCD assessment in infants, and perhaps other pulmonary diseases with a link to low nNO. With early assessments, earlier clinical intervention may be possible to slow disease progression and help reduce pulmonary morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Measurement of nNO in young children is possible, however discrimination between PCD patients and controls is reduced as nNO is inversely proportional to age in healthy patients under 12 years[28, 29]. One study showed that velum closure was possible in children as young as 3.9 years [20].…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of nNO in young children is possible, however discrimination between PCD patients and controls is reduced as nNO is inversely proportional to age in healthy patients under 12 years[28, 29]. One study showed that velum closure was possible in children as young as 3.9 years [20].…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Infants were classified as having normal or low nNO based on the published prediction interval of normative infant nNO values. 12…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Our patient cohort had a median PLOS of 15 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] days ( Table 2). The median total CICU LOS was 8 [5][6][7][8][9][10][11] days, and initial CICU LOS was 7 [5][6][7][8][9][10][11] days.…”
Section: Postoperative Outcome Assessmentsmentioning
confidence: 99%
“…19 nNO values (nl/min) were acquired using a CLD88sp chemiluminescence NO analyzer (EcoPhysics, Ann Arbor, MI). Patients were categorized as having normal or low nNO based on established cutoff values from the literature 17, 18, 20…”
Section: Methodsmentioning
confidence: 99%